Detailed Theoretical Model for Adjustable Gain-Clamped Semiconductor Optical Amplifier - Lin Liu; Craig Michie; Anthony E. Kelly; Ivan Andonovic (International Journal of Optics)
The adjustable gain-clamped semiconductor optical amplifier (AGC-SOA) uses two SOAs in a ring-cavity topology: one to amplify the signal and the other to control the gain. The device was designed to maximize the output saturated power while adjusting gain to regulate power differences between packets without loss of linearity. This type of subsystem can be used for power equalisation and linear amplification in packet-based dynamic systems such as passive optical networks (PONs). A detailed theoretical model is presented in this paper to simulate the operation of the AGC-SOA, which gives a better understanding of the underlying gain clamping mechanics. Simulations and comparisons with steady-state and dynamic gain modulation experimental performance are given which validate the model.